A volta para casa : patriarcalismo e violência em Lavoura Arcaica, de Raduan Nassar - Cordeiro, Leandra Postay (2017)
This study aims to analyze the book Lavoura arcaica, by Raduan Nassar, published in 1975, from a historiographical perspective, guided mainly by Theodor W. Adorno's ideas. The nassarian narrator and protagonist, André, who falls in love with his sister, Ana, lives in conflict with paternal values. Lavoura arcaica's scenario has traits that evoke a patriarchal society, favoring the emergence of violence, not only symbolic. Adorno suggests a connection between art and society. Following that same line of thought, we intend to analyze patriarchy and violence in Lavoura arcaica and to verify its ruptures and continuities in the story.